Analisis Residu Pestisida Profenofos pada Jeruk Manis di Kecamatan Dau, Malang - Sumiati, Astri ; Prakoso Julianto, Reza Dwi (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2018)
Citrus is one type of fruit that is highly favored by the people. Continuous use of pesticides can have a negative impact on the environment and people. Profenofos pesticides are used to control pests in citrus plants. The aims of this study is to identify and qualitatively analyze pesticide residues in citrus fruits in District of  Dau, Malang. The sample of this research is 3 kg of citrus fruit produced by 3 farmers and 3 kg of citrus fruit produced by 3 traders of Tegalwaru Village, Dau District, Malang. Qualitative analysis of pesticide residue is known based on profenofos retention time of High Performance Liquid Chromatography (HPLC) at PT. Angler Biochem Lab. The results showed that the residual level of profenofos in the farmer sample was found 0.108 ppm higher than the merchant sample of 0.050 ppm.